Evaluation of the Antifertility Effect and Toxicity of Areca nut as Oral Contraceptive: Study on Male Rats - Ave Olivia Rahman; Hasna Dewi; Billi Brian Geniro; Easti Vishiara Amdely (Jurnal Kedokteran Brawijaya, 2022)
Currently, very few male contraceptive methods are available. Areca nuts are known to have an antifertility effect, but the effective, safe dose is not certainly known. Data on its effectiveness and safety are needed to develop the potential of the areca nuts as an herbal contraceptive in men. This study determines the antifertility effect of areca nut administration at doses of 40, 30, and 20 mg/kgBW and their safety on the kidneys and liver. The green-colored raw areca nuts were used. The treatment groups were male rats whose fertility status was known before treatment. The control group were given distilled water. The treatment were given one dose a daily dissolved for 28 days of treatment, then male rats were bred again. Rats were terminated for histopathological examination of liver, kidneys, testes, and for analysis of spermatozoa. The administration of areca nuts caused a decreasing number of litters, but only the group given 40 mg/kgBW dose had a significant decrease (p<0.05). There were a damaged testes, a decreasing number and motility of spermatozoa as well as increasing spermatozoa abnormalities. There were no changes in liver tissue, but there was a mild grade cast in kidney tissue. Areca nut have antifertility effect in male rats with dose dependent manner, histopathological examination revealed cast nephotoxic but not hepatotoxic.